(untitled) (Indo-MathEdu Intellectuals Journal, 2023)
The active development of the potential of students to possess spiritual strength, self-control, personality, intelligence, noble character, and the skills needed for themselves, society, the nation, and the state is the established goal of education. The objective of this research is to identify issues related to the difficulties in early reading among first-grade students. In this study, the researcher employed a qualitative descriptive research design. The subjects of this research were 18 first-grade students from State Elementary School 064982 Medan Helvetia. The research results indicate that the highest difficulty aspect for students in early reading is difficulty in listening and comprehending the content of the reading, with a score of 13%. The next difficulty in early reading is in the aspect of reading aloud fluently, with a score of 33%. Another difficulty experienced by students is reading meaningless words, accounting for 39%. Following that, the difficulty in reading individual words is at 47%. The last aspect of difficulty in reading is identifying letters, with a score of 78%.